R Tutorial: Detection of Differentially Interacting Chromatin Regions From Multiple Hi‐C Datasets. Issue 1 (24th May 2019) - Stansfield, John C.; Tran, Duc; Nguyen, Tin; Dozmorov, Mikhail G.
Abstract: The three‐dimensional (3D) interactions of chromatin regulate cell‐type‐specific gene expression, recombination, X‐chromosome inactivation, and many other genomic processes. High‐throughput chromatin conformation capture (Hi‐C) technologies capture the structure of the chromatin on a global scale by measuring all‐vs.‐all interactions and can provide new insights into genomic regulation. The workflow presented here describes how to analyze and interpret a comparative Hi‐C experiment. We describe the process of obtaining Hi‐C data from public repositories and give suggestions for pre‐processing pipelines for users who intend to analyze their own raw data. We then describe the data normalization and comparative analysis process. We present three protocols describing the use of the multiHiCcompare, diffHic, and FIND R packages, respectively, to perform a comparative analysis of Hi‐C experiments. Finally, visualization of the results and downstream interpretation of the differentially interacting regions are discussed. The bulk of this tutorial uses the R programming environment, and the processes described can be performed with most operating systems and a single computer. © 2019 by John Wiley & Sons, Inc.